Development of Innovative Teaching Materials: Transformation of Nahwu Textbooks in Interactive Digital - Yasmadi, Yasmadi; Husna, Ilya; Lestari, Sri Indah; Afril, Rezkya (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2025)
Traditional Nahwu (Arabic syntax) teaching materials often lack interactivity and fail to engage students, leading to difficulties in grasping complex grammatical concepts. To address this gap, this research and development (R&D) study aimed to design and evaluate interactive digital-based Nahwu teaching materials. Following the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the study involved needs analysis, prototype design, and trials with students and lecturers. The findings demonstrate that the developed digital resource, enriched with quizzes, animations, explanatory videos, and educational games, significantly enhances student engagement, motivation, and conceptual understanding. This study confirms the effectiveness of interactive digital tools in Arabic language education and contributes a validated model for innovating Nahwu instruction.